Assessment and optimisation of business opportunities for telecom operators in the cloud value network. Issue 5 (19th June 2013) - Nesse, P.J.; Svaet, S.W.; Strasunskas, D.; Gaivoronski, A.A.
ABSTRACT: Cloud computing represents a major change in how resources of information technology are delivered and consumed and will influence the telecom industry, its future services, business offerings and economics of the telecommunication. New revenues potentials from mediating cloud‐based services are however less discussed, as well as the commonly accepted and completed methodology for this purpose is lacking. The objective of this paper is to clearly identify recommended roles for telecommunication companies (telcos) in the cloud value chain and to present a model for assessing and optimising innovative business opportunities. In particular, we show how the portfolio theory of modern investment science supports risk management in operation of telecom company‐based cloud carriers for service brokering. We recommend a combined broker and carrier role to be a preferred cloud business model for a telco. Such combination is expected to represent the best value proposition for competing against cloud providers and ICT integrators. Further quantitative analysis indicates significant business benefits from differentiating and optimising provision of carrier grade and best effort network connectivity types for a given bundle of cloud services. This implies an efficient use of telco assets and satisfies an increasing demand for network performance in the business market. The novelty of the paper is the developed quantitative optimisation model as well as the analytical identification of the preferred telco role in cloud value network. Practical application of the research may improve dimensioning of technological assets, leading to higher cost efficiency and possibly higher degree of customer satisfaction. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : In the paper, we argue for an innovative combination of broker and carrier roles to be a preferred cloud business model for telecom operators, as this represents the best value proposition for competing against cloud providers and ICT integrators. Then, we analyse the trade‐off between profit and risk offering a portfolio of connectivity types for the delivery of brokered cloud services. Evaluation of the results indicates significant benefits from differentiating and optimising provision of carrier grade and best effort connectivity types.